Congenital iRHOM2 deficiency causes ADAM17 dysfunction and environmentally directed immunodysregulatory disease - ÖZEN, AHMET OĞUZHAN; AYDINER, ELİF; BARIŞ, SAFA (My University, 2022)
We report a pleiotropic disease due to loss-of-function mutations in RHBDF2, the gene encoding iRHOM2, in two kindreds with recurrent infections in different organs. One patient had recurrent pneumonia but no colon involvement, another had recurrent infectious hemorrhagic colitis but no lung involvement and the other two experienced recurrent respiratory infections. Loss of iRHOM2, a rhomboid superfamily member that regulates the ADAM17 metalloproteinase, caused defective ADAM17-dependent cleavage and release of cytokines, including tumor-necrosis factor and amphiregulin. To understand the diverse clinical phenotypes, we challenged Rhbdf2-/- mice with Pseudomonas aeruginosa by nasal gavage and observed more severe pneumonia, whereas infection with Citrobacter rodentium caused worse inflammatory colitis than in wild-type mice. The fecal microbiota in the colitis patient had characteristic oral species that can predispose to colitis. Thus, a human immunodeficiency arising from iRHOM2 deficiency causes divergent disease phenotypes that can involve the local microbial environment.